Volver a Cicerón. Una propuesta de lectura de Cicerón en clave de reconocimiento político = Back to Ciceron. A proposed reading of Cicero in the key of political recognition (2017)
After the presentation of a brief definition of political recognition, it is shown why the political identity of subjects and communities is being challenged by social processes. social processes, including the current phenomenon of globalization. of globalization. This problematic horizon justifies the exploration of Cicero's thought. Cicero's thought, who is confronted with an analogous context of decadence and plural fragmentation of the polis. of decadence and plural fragmentation of the Greek polis. From there, a hermeneutic approach is made to his positioning in this context, which advocates an expansion of the sense of belonging to the polis. of the sense of belonging to the community beyond the strictly political limits. strictly political limits. This becomes a source of inspiration to rethink a moral and political theory of recognition in the contemporary world